Robot-assisted surgery for women with endometrial cancer: Surgical and oncologic outcomes within a Belgium gynaecological oncology group cohort. Issue 5 (May 2021) - Kakkos, A.; Ver Eecke, C.; Ongaro, S.; Traen, K.; Peeters, F.; Van Trappen, Ph; Laenen, A.; Despierre, E.; Van Nieuwenhuysen, E.; Vergote, I.; Goffin, F.
Abstract: Objective: To evaluate surgical and oncologic outcomes of patients treated by robot-assisted surgery for endometrial cancer within the Belgium Gynaecological Oncology Group (BGOG). Study design: We performed a retrospective analysis of women with clinically Stage I endometrial cancer who underwent surgical treatment from 2007 to 2018 in five institutions of the BGOG group. Results: A total of 598 consecutive women were identified. The rate of conversion to laparotomy was low (0.8%). The mean postoperative Complication Common Comprehensive Index (CCI) score was 3.4. The rate of perioperative complications did not differ between age groups, however the disease-free survival was significantly lower in patients over 75 years compared to patients under 65 years of age ( p=0.008 ). Per-operative complications, conversion to laparotomy rate, post-operative hospital stay, CCI score and disease-free survival were not impacted by increasing BMI. Conclusion: Robot-assisted surgery for the surgical treatment of patients suffering from early-stage endometrial cancer is associated with favourable surgical and oncologic outcomes, particularly for unfavourable groups such as elderly and obese women, thus permitting a low morbidity minimally-invasive surgical approach for the majority of patients in expert centres.